UMP organizes Pekan Bridge Run to promote a healthy lifestyle - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 10 July 2023 - Universiti Malaysia Pahang (UMP) will be organizing the UMP Pekan Bridge Run for the first time on 2 September 2023 to promote a healthy lifestyle among UMP residents and the local community.